2020
DOI: 10.1002/iub.2373
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SARS CoV2 (Indian isolate) genome with miRNA: An in silico study

Abstract: The newly identified SARS CoV2 has become a global pandemic since December 2019. Various researchers are trying to design a vaccine candidate against the virus. On the other hand, another group is focussing on repurposing approved or clinically tested drugs for treatment. However, there is always a search for alternative therapies. Thus, we propose an alternative approach apart from chemotherapy that is the usage of miRNA as novel antisense therapy to cure SARS CoV2 infected patients. To address the objective,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Several in silico studies are being undertaken to investigate the miRNA that can potentially aid in COVID-19 management (Fig. 4 ) [ 84 86 ]. For instance, in silico analysis done by Schultz et al reported the capability of MSC-EVs miRNA to modulate the increased cytokines, cell death and coagulation disturbs caused by COVID-19 [ 87 ].…”
Section: Stem Cell-derived Extracellular Vesicles In Covid-19 and Acu...mentioning
confidence: 99%
“…Several in silico studies are being undertaken to investigate the miRNA that can potentially aid in COVID-19 management (Fig. 4 ) [ 84 86 ]. For instance, in silico analysis done by Schultz et al reported the capability of MSC-EVs miRNA to modulate the increased cytokines, cell death and coagulation disturbs caused by COVID-19 [ 87 ].…”
Section: Stem Cell-derived Extracellular Vesicles In Covid-19 and Acu...mentioning
confidence: 99%